Enzymatic synthesis of nucleobase-modified UDP-sugars: scope and limitations. (2nd March 2015) - Wagstaff, Ben A.; Rejzek, Martin; Pesnot, Thomas; Tedaldi, Lauren M.; Caputi, Lorenzo; O'Neill, Ellis C.; Benini, Stefano; Wagner, Gerd K.; Field, Robert A.
Graphical abstract: Highlights: Enzymatic conversion of 5-aryl-substituted UTP to UDP-galactose derivatives. UDP-glucose pyrophosphorylase was particularly effective. Epimerization of 5-substituted UDP-glucoses with Erwinia UDP-glucose 4″-epimerase. Abstract: Glucose-1-phosphate uridylyltransferase in conjunction with UDP-glucose pyrophosphorylase was found to catalyse the conversion of a range of 5-substituted UTP derivatives into the corresponding UDP-galactose derivatives in poor yield. Notably the 5-iodo derivative was not converted to UDP-sugar. In contrast, UDP-glucose pyrophosphorylase in conjunction with inorganic pyrophosphatase was particularly effective at converting 5-substituted UTP derivatives, including the iodo compound, into a range of gluco -configured 5-substituted UDP-sugar derivatives in good yields. Attempts to effect 4″-epimerization of these 5-substituted UDP-glucose with UDP-glucose 4″-epimerase from yeast were unsuccessful, while use of the corresponding enzyme from Erwinia amylovora resulted in efficient epimerization of only 5-iodo-UDP-Glc, but not the corresponding 5-aryl derivatives, to give 5-iodo-UDP-Gal. Given the established potential for Pd-mediated cross-coupling of 5-iodo-UDP-sugars, this provides convenient access to the galacto -configured 5-substituted-UDP-sugars from gluco -configured substrates and 5-iodo-UTP.